Cognitive Behavior Group Counseling in Overcoming Academic Anxiety of Vocational Students - Habsy, Bakhrudin All; Wiryanto, W; Omoyemiju, Michael Adeniyi (Universitas Negeri Padang, 2024)
Academic anxiety is characterised by the presence of internal thoughts and sentiments of fear and doubt regarding an individual's capacity to successfully complete assignments and examinations with expected results. The Cognitive Behaviour Group Counselling (CBGC) approach is an efficient method that can assist students in addressing these difficulties more effectively. When conducting this study, a quantitative technique was utilised, and a genuine experimental design was utilised. Thirty students from vocational high schools in Mojokerto, Indonesia participated in the study. The sample size was twenty-two students, and they were split evenly between two groups: an experimental group and a control group, each consisting of eleven students. A scale for measuring academic anxiety that was based on Ottens' theory was used to collect data, and it was distributed through Google Forms. A paired sample t-test analysis was utilised in order to carry out the data analysis. When the experimental group was compared to the control group, the results showed that the experimental group saw a considerable drop in degrees of academic anxiety. The results of this study suggest that CBGC is an effective method for lowering academic anxiety among students who are enrolled in vocational colleges.